Synthesis and characterization of cerium- and lanthanum containing bioactive glass - Ershad M.; Vyas V.K.; Prasad S.; Ali A.; Pyare R. (My University, 2025)
Synthesis and characterization of bioglass® of general composition (45-X-Y) SiO2, 24.5 Na2O, 24.5 CaO and 6.0 P2O5 (wt %) was modified by addition of X= (0-1) wt % of CeO2 and Y= (0-1) wt % of La2O3 respectively. These five samples were prepared in alumina crucible via melting route at a temperature of 1400±5 °C with air as a furnace atmosphere. These glass samples were immersed in simulated body fluid (SBF) for different time period and their bioactivity were determined by Fourier transform infrared spectroscopy (FTIR) analysis. Surface morphology was studied by using Scanning electron microscope (SEM). Bioactivity, pH measurement of bioactive glass was carried out and mechanical properties of these glasses increased with increasing concentration of CeO2 and La2O3. © 2017 Trans Tech Publications, Switzerland.